KEMAMPUAN BERBICARA BAHASA INGGRIS SISWA DALAM BERCERITA KEGIATAN SEHARI-HARI DI SMPN 1 RANAH PESISIR - Yola Melshandika; Dian Riani; Revi Handayani; Risma Wiwita; Taufik Abdul Hasan (JURNAL MANAJEMEN PENDIDIKAN, 2022)
The aim of this study was to describe the speaking ability of the first grade students at SMPN 1 Pesisir in telling their daily activities. The design of this study was descriptive method. Cluster random sampling was used to select the sample. The total number of sample was 62 students’. The data were collected through speaking test. The data was measured by considering five components of speaking. Based on the findings of this study, students speaking ability were low. The findings were proved by the evidence that 85.49% of them cannot tell their daily activities orally. Based on the findings, this study was suggested for English teachers to consider the five components of speaking when measuring students’ speaking ability and English teachers were suggested to provide more practices for those components of speaking. The students were suggested to do more practices and improve their comprehension about material especially in speaking.